An Integrative Approach for Understanding Diversity in the Punctelia rudecta Species Complex (Parmeliaceae, Ascomycota). - David Alors; H Thorsten Lumbsch; Pradeep K Divakar; Steven D Leavitt; Ana Crespo (PLoS ONE, 2016)
High levels of cryptic diversity have been documented in lichenized fungi, especially in Parmeliaceae, and integrating various lines of evidence, including coalescent-based species delimitation approaches, help establish more robust species circumscriptions. In this study, we used an integrative taxonomic approach to delimit species in the lichen-forming fungal genus Punctelia (Parmeliaceae), with a particular focus on the cosmopolitan species P. rudecta. Nuclear, mitochondrial ribosomal DNA and protein-coding DNA sequences were analyzed in phylogenetic and coalescence-based frameworks. Additionally, morphological, ecological and geographical features of the sampled specimens were evaluated. Five major strongly supported monophyletic clades were recognized in the genus Punctelia, and each clade could be characterized by distinct patterns in medullary chemistry. Punctelia rudecta as currently circumscribed was shown to be polyphyletic. A variety of empirical species delimitation methods provide evidence for a minimum of four geographically isolated species within the nominal taxon Punctelia rudecta, including a newly described saxicolous species, P. guanchica, and three corticolous species. In order to facilitate reliable sample identification for biodiversity, conservation, and air quality bio-monitoring research, these three species have been epitypified, in addition to the description of a new species.